The impact of socialist legacy on regional differences in innovation activities and cooperation in Europe: A mediation analysis - Michael Fritsch; Maria Greve; Michael Wyrwich (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2025)
This paper examines how the legacy of socialist regime in countries of Central and Eastern Europe has affected innovation and R&D cooperation and compares this to Western Europe. Our analysis reveals that the negative impact of socialism on innovation Central and Eastern European countries is mediated by interpersonal trust and the quality of government. These findings highlight the significance of historical context for innovation activity. Our insights are particularly relevant for policymakers who are trying to create effective strategies to encourage technological development in post-socialist regions.
Keywords: O31; O43; P20; R11; 330; Innovation; socialist legacy; institutional quality; trust